EKSTRAK ETANOLIK DAUN AWAR–AWAR (Ficus septica Burm. f.) MEMACU APOPTOSIS SEL KANKER PAYUDARA MCF-7 MELALUI PENEKANAN EKSPRESI Bcl-2 - Dewi Arum Sekti; Muhammad Fithrul Mubarok; Inna Armandani; Sendy Junedy; Edy Meiyanto (Faculty of Pharmacy, Universitas Gadjah Mada, 2010)
Alkaloid fenantroindolisidin showed cytotoxic activity against several cancer cells. Ethanolic leaf extract of Awar-awar proven to increase the cytotoxic activity of chemotherapy agent doxorubicin in MCF-7 cells. This study aims to determine the effect of Ethanolic leaf extract of Awar-awar in apoptosis induction of breast cancer cells MCF-7.Awar-awar leaf powder was extracted by maceration using 70% ethanol and then concentrated to obtain concentrated of Awar-awar. Apoptosis induction was examined by double staining method and the expression of Bcl-2 protein was observed by immunohistochemistry method. Single treatment of Awar-awar leaf extract showed the ability of extracts to induce apoptosis and downregulated the expression of Bcl-2 protein. Ethanolic leaf extract of Awar-awar is potential as co-chemotherapeutic agent.